Determination of Environmental Exposure to Microcystin and Aflatoxin as a Risk for Renal Function Based on 5493 Rural People in Southwest China - Lin, Hui; Liu, Wenyi; Zeng, Hui; Pu, Chaowen; Zhang, Renping; Qiu, Zhiqun; Chen, Ji-an; Wang, Lingqiao; Tan, Yao; Zheng, Chuanfen; Yang, Xiaohong; Tian, Yingqiao; et al. (Environmental science & technology, 2016)
Although the nephrotoxicity of microcystin and aflatoxin has been observed in animal and clinical cases, few population data are available. We conducted a cross-sectional study in Southwest China to investigate the association of renal function indicators (RFIs, including BUN, SCr, and eGFR) with exposure to microcystin and aflatoxin in 5493 members of the general population. Microcystin-LR levels in water and aquatic products and aflatoxin B1 levels in daily foods were measured by ELISA, and individual estimated daily intake (EDI) was assessed on the basis of the measurement and questionnaire. We found that participants with abnormal RFIs had a much higher mean level of microcystin-LR EDI than those with normal RFIs and that there was a significant increasing trend for abnormal rates and odds ratios of RFIs with increasing microcystin-LR EDI quartiles (p for trend = 0.000). Compared with the lowest quartile of microcystin-LR exposure, those in the highest quartile had significantly higher risks of abnormal BUN (OR = 1.80, 95% CI = 1.34–2.42), SCr (OR = 4.58, 95% CI = 2.92–7.21), and eGFR (OR = 4.41, 95% CI = 2.55–7.63), respectively, but no higher risk was found in subjects with higher AFB1 exposure. After adjustment for confounding factors, risk associations with microcystin-LR persisted. Consequently, our results suggest that microcystin, rather than aflatoxin, might be one important risk of renal-function impairment.